KI-67 PROLIFERATING INDEX AND HISTOLOGICAL GRADE, TYPE AND STAGE OF COLORECTAL CARCINOMA - Nabi, Uzma; Nagi, A H; Sami, Waqas (Journal of Ayub Medical College Abbottabad, 2008)
Background: The objective of this study was to assess the relationship of histological type, grade and stage of colorectal carcinoma with proliferative activity as measured by Ki-67 LI. It was a descriptive study and conducted at the Department of Pathology, University of Health Sciences, Lahore. Methods: Ki-67 is a protein associated with cell proliferation and is expressed in all the phases of cell cycle except G0. In the present study, Ki-67 expression in 50 patients with colorectal adenocarcinomas was observed using immunohistochemistry with monoclonal antibody MIB-1. Results: Ki-67 LI was high in well and moderately differentiated adenocarcinomas (mean Ki-67 LI 392.50± 56.58 and 342.24±96.84 respectively) as compared to poorly differentiated adenocarcinomas (mean Ki-67 LI 250.00±113.46). Ki- 67 LI was high in non mucinous adenocarcinomas than mucin secreting and signet ring cell adenocarcinomas (mean Ki-67 393.93±55.91 vs 220.00±49.72 and 200.00±79.05 respectively). As regard the Dukes' staging, Ki-67 LI was high in colorectal carcinomas in Dukes' stage B than tumours in Dukes' stage C (Mean Ki-67 LI 360.13±90.03 vs 241.66±101.31 respectively). Conclusion: The proliferative activity as measured by Ki-67 antibody is related to histological type, grade and stage. Keywords: Colorectal carcinoma, Grade, Proliferation index, Immunohistochemistry, Ki-67